URGENSI INTEGRASI DAN IMPLEMENTASI MASLAHAH DALAM PROSES MEDIASI - Moh Ali (Al'Adalah, 2019)
Mediation in the judiciary in Indonesia is still new, cases that are in court must be handled professionally, such as family case. This has claimed many victims, both material and life. This study is the orientation of mediation rules and their implications for the settlement of civil cases in the Religious Courts. There are three important aspects that will be discussed in this research, these are Juridicalphilosophical foundation for integrating mediation in the proceedings at the Religious Courts, The implementation of mediation in the Religious Courts, maslahah analysis on the integration of mediation in the proceedings at the Religious Courts. This research is socio-legal qualitative research because it is closely related to the study of the texts in the legislation; by using a state approach and focusing on legal norms and the hierarchy of the rules. The result of this research reveals that; (1) The juridical-philosophical foundation integrated with mediation in the proceedings at the Religious Courts, which is based on PERMA No. 1 of 2008, the mediator of the Religious Court then integrates into facilitative mediation and transformative mediation model. (2) Mediation conducted by the Religious Courts does not only discuss problems that occur, but also discuss the root of the problem and making solutions that cannot only be completed in the trial, and also bring benefits to the disputing parties. (3) In general, the integration of mediation in proceedings process in the Religious Court is in Maslahah's perspective, with the existence of Maslahah, by utilizing Al-Maslahah Al- Mu'tabarah, such as; by hastening the implementation of divorce (wife), as a form of state protection to prevent the emergence of suffering and the madharat of both parties. Protection of the soul, to avoid the tyranny of others. Become a catalyst so that the parties become easy to live and protracted problems to realize the path of peace. Protection of human dignity, by making a decision to cancel the marriage for the Plaintiff who as given a false identity.